The Analysis of Teaching Writing Descriptive Text at the Seven Grade of Junior High School: Analisis Pembelajaran Menulis Teks Deskriptif Pada Siswa Kelas Tujuh SMP - Fadli Ganing; Vidya Mandarani (Academia Open, 2021)
This study aims to identify and describe the learning process and the problems faced by teachers in teaching writing descriptive texts in the seventh grade of SMP Negeri 2 Candi. The method in this study is a qualitative descriptive method. In collecting data, researchers used interviews and document studies. The results showed that the learning process of writing descriptive text by the teacher in class seven grade of SMP Negeri 2 Candi consisted of preliminary activities, core activities, and closing activities. The teaching process carried out by the teacher is still effective. The teacher has planned the learning process, selected materials, prepared activities and roles, and evaluated learning. Then, the problem of the teacher in the teaching process of writing descriptive text comes from external factors, namely the students. students have problems in developing their ideas in writing, they have a lack of vocabulary and students have difficulties in grammar.